The Application of Youtube Video To Improve Students’ Speaking Skill At The 7th Grade of SMP Negeri 1 Tiakur Maluku Barat Daya - Nederupun, Aleda Fenska; Lekatompessy, J; Tiwery, Yulina (Prodi Pendidikan Bahasa Inggris, Program Studi Diluar Kampus Utama (PSDKU) Unpatti-MBD, 2023)
This study aimed to help students in the 7th Grade of SMP Negeri 1 Tiakur improve their speaking skills through the application of YouTube videos and find out the students'students' responses about the application of YouTube videos in helping them to improve their speaking skills. This research was conducted at SMP Negeri Tiakur Maluku Barat Daya; the research employed Classroom Action Research (CAR), which involves four stages: planning, acting, observing, and reflecting in each cycle. The data collected included tests, questionnaires and observations. Test results showed a notable improvement in speaking scores. Initially, none of the students passed the minimum mastery criterion (KKM) in the pre-test, with a mean score of 50,77%. By the second cycle'scycle's post-test, all students achieved a score above the minimum criterion, with a mean score of 76,15%. This substantial improvement suggests that the use of YouTube videos was a good method for enhancing students' speaking skills. The findings indicated that using YouTube videos to improve students'students' speaking skills was effective.